Analysis of the Effectiveness of the Problem Base Learning Learning Model on Students' Problem Solving Ability in Sociology Subject in Class X of SMAN 2 Pangkep - A Octamaya Tenri Awaru; Husnul Khotibah; Imawar; Muh. Nur Fatwa (PT FORMOSA CENDEKIA GLOBAL, 2023)
This article's goal is to learn more about the base learning issue learning model's applicability, student problem abilities, and effectiveness of the learning problem problem problem on the efficacy of the sman 2 students' problem. The study used motode a survey spread through Google form with a descriptive quantitative type. The results of this study indicate that the problem baselearning's application of the learning model is in the good category (52.8%), the student's ability is the problem is in good category (38.9%), and a sig value table of 0.001 which shows that the problem of base learning affects the ability of student problems, Rsquare value table of 0297 or 29.7% which suggests that variables of based learning problems affect 29.7% 'student ability. Overall, it could be drawn the conclusion that using the learning issue learning model has an effectiveness on the ability of the SMAN 2 Pangkep.